Partial root-zone drying subsurface drip irrigation increased the alfalfa quality yield but decreased the alfalfa quality content - Wang, Yadong; Xu, Chong; Gu, Qian; Shi, Yalong; Chen, Jiale; Wu, Honghui; He, Jing; Li, Xingfu; Han, Liliang; Su, Derong (Frontiers in Plant Science, 2024)
Water shortage seriously restricts the development of grassland agriculture in arid land, and dramatically impacts alfalfa (Medicago sativa L.) quality content and hay yield.Reasonable irrigation methods have the potential to enhance can improve alfalfa quality content, hay yield, and thus quality yield. Whether partial root-zone drying subsurface drip irrigation (PRDSDI)(PRD) improves alfalfa quality yield, quality content, and hay yield is still unknown compared to conventional subsurface drip irrigation (CSDI). The effects of PRDSDIPRD compared with CICSDI and the interaction with irrigation volume (10, 20, and 30 mm/week) on alfalfa quality yield were investigated in 2017-2018 and explained the change in quality yield with alfalfa quality content and hay yield. Here the results showed that PRDPRDSDI did not increase alfalfa quality yield in two years. PRDPRDSDI significantly increased acid detergent fiber by 13.3 % and 12.2 % in 2018 with 10 and 20 mm irrigation volumes and neutral detergent fiber by 16.2, 13.2, and 12.6 % in 2017 with 10, 20, and 30 mm irrigation volumes, respectively. PRDPRDSDI significantly decreased the crude protein by 5.4 % and 8.4 % in 2018 with 10 and 20 mm irrigation volumes and relative feed value by 15.0 % with 20 mm irrigation volume in 2017 and 9.8 % with 10 mm irrigation volume in 2018, respectively. In addition, PRDPRDSDI significantly increased the alfalfa average hay yield by 49.5 and 59.6 % with 10 and 20 mm irrigation volumes in 2018, respectively. Our results provide a counterexample for PRDPRDSDI to improve crop quality. Although there was no significant improvement in average quality yield by PRDPRDSDI, the positive impact of average hay yield on quality yield outweighed the negative impact of quality content. Thus has the potential to improve quality yields. The novel findings regarding the effect of PRDPRDSDI on quality yield be potentially favorable for the forage feed value in water-limited areas.